Global trends in recombinant human growth hormone for the treatment of idiopathic short stature: a bibliometric analysis - Ouyang, Rong; Gu, Haiyun; Yuan, Jie; Sun, Yi; Zhao, Xiaoqin (Frontiers in Medicine, 2025)
BackgroundThe treatment of idiopathic short stature (ISS) with recombinant human growth hormone (rhGH) has been a subject of extensive research. This study aims to perform a bibliometric analysis of publications related to rhGH treatment for ISS, identifying research hotspots, key publications, and international collaboration networks.MethodsA literature search was conducted on the Web of Science Core Collection, covering literature from 1991 to 2024. Bibliometric tools including CiteSpace, VOSviewer and “bibliometrix” package of R were used to analyze publication trends, authorship, institutional contributions, and citation networks. Keyword co-occurrence and burst detection were performed to identify emerging research topics.ResultsThis area of study had experienced significant growth and maturation over the past three decades, characterized by increasing interest and investment in research pertaining to rhGH interventions for ISS. The majority of research output was concentrated in China. Leading contributors to this body of work included the University of Ulsan. The most prolific academic journals in this field were the Journal of Clinical Endocrinology & Metabolism. The keyword co-occurrence analysis identified “gene,” “mutations,” and “genotype,” highlighting genetic factors in rhGH therapy for ISS. Keyword burst analysis, however, emphasized recent trends like “safety” and “growth hormone deficiency,” reflecting growing attention to treatment risks and patient-specific care.ConclusionThis bibliometric analysis highlights the progression of rhGH research for ISS, shifting from foundational studies to contemporary priorities such as tailored therapies and clinical outcomes. Future research should focus on advancing precision medicine and optimizing treatment protocols while addressing safety concerns and long-term effectiveness.